2010
DOI: 10.1162/jocn.2009.21318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COMT Gene Polymorphism on fMRI-assessed Sustained and Transient Activity during a Working Memory Task

Abstract: The catechol O-methyltransferase (COMT) gene--encoding an enzyme that is essential for the degradation of dopamine (DA) in prefrontal cortex (PFC)--contains a single nucleotide polymorphism (val/met) important for cognition. According to the tonic-phasic hypothesis, individuals carrying the low-enzyme-activity allele (met) are characterized by enhanced tonic DA activity in PFC, promoting sustained cognitive representations in working memory. Val carriers have reduced tonic but enhanced phasic dopaminergic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 67 publications
6
55
1
2
Order By: Relevance
“…The present results converge with findings of previous studies (e.g., de Frias et al, 2009) in suggesting that to achieve the same level of performance as younger adults and COMT Met carriers, older adults and COMT Val carriers need to recruit the DLPFC to a high degree already during WM maintenance. Lowered dopamine for older adults and COMT Val carriers could impair sustained DLPFC processing via D1 receptors during the delay phase (Cohen, Braver, & Brown, 2002), which cascades into stronger DLPFC engagement during maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…The present results converge with findings of previous studies (e.g., de Frias et al, 2009) in suggesting that to achieve the same level of performance as younger adults and COMT Met carriers, older adults and COMT Val carriers need to recruit the DLPFC to a high degree already during WM maintenance. Lowered dopamine for older adults and COMT Val carriers could impair sustained DLPFC processing via D1 receptors during the delay phase (Cohen, Braver, & Brown, 2002), which cascades into stronger DLPFC engagement during maintenance.…”
Section: Discussionsupporting
confidence: 92%
“…From previous studies that investigated the effect of COMT effect on n-back performance (Egan et al 2001 ;Stefanis et al 2004 ;Bruder et al 2005 ;Bertolino et al 2006 ;Caldu et al 2007 ;de Frias et al 2010), only one found a significant effect, with Met/Met homozygotes performing better than the rest (Goldberg et al 2003). However, the n-back task used in their study required individuals to respond to each stimulus whereas our study did not (Goldberg et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, we cannot rule out the possibility that the phasic dopamine effect is very tenuous [see for example (Rosa, et al, 2010)], that other genes than COMT are related to the phasic component of dopamine regulation [see for example (Bilder, et al, 2004)] or that our procedure was not perfectly designed to evidence the distinction between tonic/phasic dopaminergic regulation [for a clearer distinction between these two regulation systems see (de Frias, et al, 2010)]. …”
Section: How To Explain the Positive Effect Of Met Genotype Loading Omentioning
confidence: 99%